Case-report: Metastases in a low-stage middle-graded HCC in cleared HCV infection, non-cirrhotic liver: Surgical therapy. (2018) - Brozzetti, Stefania; Bini, Simone; Fazzi, Katia; Chiarella, Leonardo Luca; Ceccarossi, Virginia; De Lucia, Chiara; De Toma, Giorgio
Highlights: HCC metastases have commonly poor prognosis and bad QoL. Therapy is only palliative. Different microinvasive surgical-radiological approaches are possible in indolent HCC. Patient achieved impressive long survival and maintained a sporty life. In methacronous-oligometastatic disease only-surgical therapy shall be evaluated. Abstract: Introduction: Hepatocellular carcinoma (HCC) is rare in non-cirrhotic liver. Achievement of sustained virological response (SVR) reduces even more the risk. Presentation of case: Liver resection for small HCC was performed in cleared HCV infection non-cirrhotic 62-year-old man. Methacronous oligometastatic recurrences in intolerant to Nexavar ® side-effects patient, were treated by multiple innovative microinvasive approaches: bilateral laparoscopic adrenalectomy, thoracic wall resection, laparoscopic sacrum cryoablation combined with hadron-therapy. Discussion: Therapies allowed the patient to lead 6 years satisfying QoL with only a small residual presacral disease stable at 8 months. Conclusion: Microinvasive surgery may be a valid resource of therapy in indolent HCC limited distant recurrences.